PERANAN PETERNAKAN AYAM BROILER PADA PLASMA PT.CIOMAS ADI SATWA TERHADAP PENDAPATAN PETERNAK (STUDI KASUS DI DESA SARANG HALANG KECAMATAN PELAIHARI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN) - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This Research aim to know technically about effort management broiler Broiler Chicken-Poultry in Plasma PT. Ciomas Adisatwa to Breeder Revenue in Sarang Halang village Sub-district Pelaihari Tanah Laut Regency South Kalimantan Province and to know about cost, acceptance, and revenue Chicken-Poultry in Plasma PT. Ciomas Adisatwa. Pursuant to result of research to effort livestock chicken broiler, Totalize product of broiler chicken is 10.200 with mean old age conservancy 31-33 day and able total of wight body 18.856 at the price of selling from Rp. 17.870/kg - Rp. 18.220/kg. Acceptance obtained Plasma of Poultry of Broiler PT. Ciomas Adisatwa equal to Rp. 338.422.335 with Total Variable Rp. 318.380.000. Earnings effort Plasma of Poultry of Broiler PT. Ciomas Adisatwa in Sarang Halang village Sub-district Pelaihari Tanah Laut Regency South Kalimantan Province equal to Rp. 20.042.335.